Technical and tactical analysis on Yuto Muramatsu vs Fan Zhengdong in final match at 2014 Youth Olympic Games - Liu, Q.; Xia. M.; Zhang, X. (Proceedings book of the 14th ITTF Sports Science Congress & the 5th World Racquet Sports Congress, Suzhou, May 23.-25. 2015, 2017)
17-years-old Yuto Muramatsu was runner-up at the 2014 Youth Olympic Games. Yuto Muramatsu won one game of Zhang Jike in the 2014 Asian Games team competition. He also has a good performance in the 2014 World Junior Table Tennis Championships. He is a chopper star in Japan. The technical and tactic of Yuto Muramatsu in the final match at 2014 Youth Olympic Games was analysed by the classic three-phase method and the Simi Scout technical and tactical analysis software. The purpose of this study was to provide a reference for Chinese table tennis players. The main conclusions were as followings: (1) Yuto Muramatsu`s serve had high quality. The drop point and rotation of the ball had a lot of changes. His serve was mainly at the backhand half-length court and long serve, combined with forehand deviation centerline short serve. He had some ability to attack after serve. (2) His Receive used backhand chopping technique more, chop long and short less. The drop point of receive was mainly in the opponent`s backhand. (3) Yuto Muramatsu had ability to change defensive to attack with huge threat of force in rally phase, which made him score directly, but error rate was high. His backhand chopping defensive was good, and forehand rally ability is poor.